Drivers of Inequality and Poverty in the CEE and other EU Member States - Sebastian Leitner; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2014)
Inequality is a multidimensional phenomenon though it is often discussed along a single dimension such as income. This is also the case for the various decomposition approaches of inequality indices by recipients or income sources. In this paper we study one- and multidimensional indices on inequality on data for CEE EU Member States in comparison to other EU countries including four dimensions in our measure of multidimensional inequality income, health, education, and housing, and apply various decomposition methods to these one- and multidimensional indices and also to a poverty index. In doing so, we apply standard decomposition techniques to the Mean logarithmic deviation index (I₀) and decompositions based on regression analysis in conjunction with the Shapley value approach to Gini indices.
Keywords: A13; D31; I32; 330; inequality decomposition; multidimensional inequality; poverty